(untitled) (Advancements in Homeopathic Research, 2022)
A Peritonsillar abscess is also known as Quinsy. It is an accumulation of pus behind the palatine tonsil due to an infection. Precisely, it is a collection of pus between the fibrous capsule of the tonsil, usually at the upper pole & the superior constrictor muscles of pharynx. The signs & symptoms of quinsy include fever, throat pain, trouble in opening mouth, redness, swelling and change in the voice. Pain is usually worse on one side. The complications may include blockage of the airway or aspiration pneumonitis. The conventional treatment is done for removing the pus by incision & drainage along with medications for swelling & pain management. The homeopathic line of treatment depends on the actual state of the condition. Homeopathic medicines can be used in mild to moderate cases of peritonsillar abscess successfully as see through this research study. In this study, 46 cases of peritonsillar abscess of age group between 5 to 80 years were included. After going through the results, it is observed that the peritonsillar abscess can be treated successfully by Homoeopathy. The scope of Homoeopathy in the treatment of peritonsillar abscess is excellent and shows high success rate of 44 out of 46 patients responding successfully to the Homoeopathic treatment with no signs of recurrence in near future. The outstanding Homoeopathic remedies in the treatment of peritonsillar abscess were found to be mostly Hepar Sulph & Merc Sol along with Calc Carb, Baryta Carb and Phytolacca. All that is required in the treatment of peritonsillar abscess is quick selection of right remedy and right dose for the instant relief rationally. Hence we can rightly claim that by proper Homoeopathic treatment we can make the world better for the future generation. This research paper will certainly help the health professionals to overcome such problems of surgical cases and consider the benefits of the facts in scope of Homoeopathy in peritonsillar abscess.